Suicidal ideation and lifetime attempts in substance and gambling disorders. Issue 3 (28th February 2015) - Manning, Victoria; Koh, Puay Kee; Yang, Yi; Ng, Andrew; Guo, Song; Kandasami, Gomathinayagam; Wong, Kim Eng
Abstract: Suicidality is more commonly reported among individuals with addictions relative to the general population, though data from Asian countries remain scarce. The medical records of 2187 Singaporean patients with drug ( n =879), alcohol ( n =754) or gambling ( n =554) disorders entering an outpatient treatment service were examined to explore differences in suicidal ideation and lifetime attempts between substance and gambling addictions. The relationship between suicidality, co-morbidity and addiction severity were also examined. 25.0% reported thoughts of suicide in the past month, 11.8% had a suicide plan and 12.2% reported lifetime attempts. Rates of suicidal ideation (thoughts, and plan) but not lifetime attempts were significantly higher among gambling than substance use patients. Co-morbid (DSM-IV axis-1) disorders were found among 32.5%, 38% and 40% of those reporting thoughts, plan and lifetime attempts respectively. Addiction severity was higher and quality of life lower among those reporting suicidal behaviors. Logistic regression revealed co-morbidity, debt, gender (being female) and being a gambling patient as significant predictors of suicidal behaviors. The findings highlight the importance of screening for suicidality, even in the absence of co-morbidity, particularly among gambling disorder patients with debts. Suicide risk should be assessed periodically and referral to suicidal prevention interventions routinely offered to this vulnerable population.